Experimental investigation of vertical and batter pile groups subjected to dynamic loads. Issue 116 (January 2019) - Bharathi, M.; Dubey, R.N.; Shukla, Sanjay K.
Abstract: In the present work, the dynamic responses of cast in-situ reinforced concrete vertical and batter pile groups constructed in the silty sand have been investigated. An experimental study was carried out on four pile groups: a group of three vertical piles and a group of three batter piles arranged in triangular pattern, and a group of four vertical piles and a group of four batter piles arranged in square pattern. All batter piles were inclined at 20° to the vertical. Each pile group had a rigid pile cap supporting the oscillator-motor assembly for generating the dynamic loads. The pile groups were tested by varying the exciting force level in different loading direction, and their responses were compared in terms of resonant frequency and peak displacement. The peak displacement of the batter pile group shows a significant reduction (about 25% and 50% in vertical and lateral directions, respectively) compared to their respective vertical pile groups. Graphical abstract: fx1 Highlights: Field experiment on cast in-situ RC vertical and batter pile groups. Effect of load intensity and excitation direction on dynamic behaviour. Comparison of dynamic responses (resonant frequency and peak displacement).